Sociodemographic and clinical characteristics and access to health care in patients with spinal muscular atrophy in Argentina - Vazquez, Gabriel Adolfo; Nasif, Salomé; Marciano, Sebastián; Pagotto, Vanina (Frontiers in Neurology, 2023)
The FAME registry gathers the majority of patients with SMA in Argentina. From it, the clinical, sociodemographic and access to treatment characteristics were analyzed in 322 patients (range 8 months-61 years) included from 2008 to 2021. Important data were obtained for the planning of medical care of these patients such as: similar distribution of patient care in public and private hospitals, time gap between onset of symptoms and diagnoses, low level of completion of SMN2 copy count, estimate of 16 new diagnoses per year between 2014 and 2018, and 68% of patient in specific pharmacological treatment.2) This study is cross-sectional, analyzing specific data at the end of it. In case of need to corroborate or update data, telephone or email contact was established. The filiation data were coded to guarantee confidentiality.3) The data were analyzed by a specialist in neuromuscular diseases. 4) Inclusion criteria: availability of confirmatory genetic test for SMA 5q-. 5) Exclusion criteria: incomplete or inconsistent data from the medical point of view after analysis by a specialist.